Collateral Recruitment Is Impaired by Cerebral Small Vessel Disease. Issue 5 (May 2020) - Lin, Michelle P.; Brott, Thomas G.; Liebeskind, David S.; Meschia, James F.; Sam, Kevin; Gottesman, Rebecca F.
Abstract : Background and Purpose—: Cerebral small vessel disease (SVD) is associated with increased stroke risk and poor stroke outcomes. We aimed to evaluate whether chronic SVD burden is associated with poor recruitment of collaterals in large-vessel occlusive stroke. Methods—: Consecutive patients with middle cerebral artery or internal carotid artery occlusion presenting within 6 hours after stroke symptom onset who underwent thrombectomy from 2012 to 2017 were included. The prespecified primary outcome was poor collateral flow, which was assessed on baseline computed tomographic angiography (poor, ⩽50% filling; good, >50% filling). Markers of chronic SVD on brain magnetic resonance imaging were rated for the extent of white matter hyperintensities, enlarged perivascular spaces, chronic lacunar infarctions and cerebral microbleeds using the Standards for Reporting Vascular Changes on Neuroimaging criteria. Severity of SVD was quantified by adding the presence of each SVD feature, with a total possible score of 0 to 4; each SVD type was also evaluated separately. Multivariable logistic regression analyses were performed to evaluate the relationships between SVD and poor collaterals, with adjustment for potential confounders. Results—: Of the 100 eligible patients, the mean age was 65±16 years, median National Institutes of Health Stroke Scale score was 15, and 68% had any SVD. Poor collaterals were observed in 46%, and those with SVD were more likely to have poor collaterals than patients without SVD (aOR, 1.9 [95% CI, 1.1–3.2]). Of the SVD types, poor collaterals were significantly associated with white matter hyperintensities (aOR, 2.9 per Fazekas increment [95% CI, 1.6–5.3]) but not with enlarged perivascular spaces (adjusted odds ratio [aOR], 1.3 [95% CI, 0.4–4.0]), lacunae (aOR, 2.1 [95% CI, 0.6–7.1]), or cerebral microbleeds (aOR, 2.1 [95% CI, 0.6–7.8]). Having a greater number of different SVD markers was associated with a higher odds of poor collaterals (crude trend P <0.001; adjusted P =0.056). There was a dose-dependent relationship between white matter hyperintensity burden and poor collaterals: adjusted odds of poor collaterals were 1.5, 3.0, and 9.7 across Fazekas scores of 1 to 3 ( P trend=0.015). No patient with an SVD score of 4 had good collaterals. Conclusions—: Chronic cerebral SVD is associated with poor recruitment of collaterals in large vessel occlusive stroke. A prospective study to elucidate the potential mechanism of how SVD may impair the recruitment of collaterals is ongoing. Abstract : Supplemental Digital Content is available in the text.